Question

( x^{2}+(sin 2-2) x-(1+sin alpha)=0 )
( alpha+beta=(sin 2-2) )
( 2 beta=-(1+sin alpha) )
et, a 2 b an the mats. ( begin{aligned}left(a^{2}+b^{4}right) &=(alpha+beta)^{2}-2 Delta beta &=(15 n 2-2)^{2}+2(1+sin alpha) end{aligned} )
( =sin ^{2} alpha+4-4 sin alpha+2+2 sin alpha )
( F sin ^{2} alpha-2 sin alpha+6 )
Stum 1
( =(1 sin alpha-1)^{2}+5 )
( (sin alpha-1)=0,+infty )
( sin ^{2}=1 )
( therefore alpha=frac{4}{2} )

# (C) 6 Q.14 If the sum of the square of the roots of the equation x2 - (sin a - 2)x - (1 + sin a) = 0) is least, then a is equal to : [AIEEE Online - 2012]

Solution